First Report of Capsule Replacement among Electrophoretic Type 37 Neisseria meningitidis Strains in Italy - Stefanelli, Paola (American Society for Microbiology, 2003)
This report describes the C-to-B capsular switching in four Neisseria meningitidis strains belonging to the electrophoretic type 37 (ET-37) complex. In particular, one strain belonged to the new sequence type 1860, which was first detected in the year 2000 in Italy and is now frequently isolated. The presence of switched serogroup B strains deserves special attention if they prove as able to spread as their serogroup C progenitors belonging to the hypervirulent ET-37 complex.